Intersecting-state model calculations on fast and ultrafast excited-state proton transfers in naphthols and substituted naphthols - Barroso, Mónica (2002)
The intersecting-state model (ISM) is applied to the calculation of absolute rate constants for proton-transfer reactions of naphthols and substituted naphthols in the first singlet state and for ground states. ISM incorporates quantum-mechanical tunnelling, zero-point energy corrections and an electrophilicity parameter to account for the lowering of the binding energy of transition states. Good agreement with experimental rates is observed over 12 orders of magnitude. The lower reactivity of the photoacids in alcohols when compared to the behaviour in water can be accounted for the differences in the potential energy curves of the OH bonds. Patterns of reactivity with respect to free-energy relations and kinetic isotope effects are also discussed.